Unmasking pulmonary hypertension following tricuspid valve replacement. Issue 1 (10th December 2020) - Ajam, Mustafa; Touma, Rabih; Chehab, Omar; Shokr, Mohamed; Abidov, Aiden
Abstract: In this Viewpoint, we highlight a possible hemodynamic problem arising following tricuspid valve replacement (TVR) in patients with severe chronic tricuspid regurgitation, represented by "unmasking" of pulmonary hypertension (PH) following the surgery. We share an observation that should alert cardiologists to the fact that this increasingly utilized surgery is not risk free, and careful assessment of the right ventricular function and pulmonary circulation preoperatively is extremely important, especially in patients with preexisting risk factors for PH, since TVR may lead to a sudden increase in right ventricular afterload.